2012
DOI: 10.1590/s0102-695x2012005000027
|View full text |Cite
|
Sign up to set email alerts
|

Sesame oil enhances endogenous antioxidants in ischemic myocardium of rat

Abstract: The present study was designed to evaluate the potency of antioxidant activity of sesame oil in-vitro model of myocardial ischemic reperfusion injury of rat. Sesame oil was administered orally to Wistar albino rats (180-200 g) in two different doses (n=6), by gastric gavage at a dose of 5 mL/kg b.w. (S1) and 10 mL/kg b.w (S2) daily for thirty days. Control and sesame oil treated rat hearts were subjected to invitro global ischemic reperfusion injury (5 min perfusion, 9 min nofl ow and 12 min reperfusion). A si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…In our previous study it was observed that the sesame oil shows protective role via enhancing the myocardial endogenous antioxidant system in the ischemic heart. 17 The same effect also observed in the present study could be an evidence for antioxidant mechanism of sesame oil as cardio protective agent.…”
Section: 33supporting
confidence: 88%
See 1 more Smart Citation
“…In our previous study it was observed that the sesame oil shows protective role via enhancing the myocardial endogenous antioxidant system in the ischemic heart. 17 The same effect also observed in the present study could be an evidence for antioxidant mechanism of sesame oil as cardio protective agent.…”
Section: 33supporting
confidence: 88%
“…Recently we found that chronic administration of sesame oil enhances the endogenous antioxidants in ischemic myocardium. 17 So, we hypothesized that the protective role of sesame oil against ISO induced myocardial injury may be via antioxidant system. Based on this hypothesis the present investigation is undertaken to find out the potency of antioxidant activity of chronic administration of sesame oil and to estimate the cardio protective action rendered by sesame oil.…”
Section: Introductionmentioning
confidence: 99%
“…[3] AESL also offered significant inhibition activity in in-vitro antioxidant model which confirmed the protective role via the antioxidant mechanism. As per phytochemical investigation, the AESL contain flavonoids and phenolic compounds in high concentrations, which might be a responsible active principle for the cardio protective action.…”
Section: Discussionmentioning
confidence: 76%
“…According to the World Health Organization report, the maximum mortality occurs within the age limit of 40-50 years due to myocardial infarction (MI) in both western and developing countries. [123] Oxidative stress due to extensive generation of free radicals with concomitant depletion of endogenous antioxidants like superoxide dismutase, catalase and reduced glutathione (GSH) play an important role in MI. [3]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation